Persistence of Good Living A'uwe Life Cycles and Well-Being in the Central Brazilian Cerrados - Welch, James R. (University of Arizona Press, 2023)
Cultural understandings of well-being often differ from scientific measures such as health, happiness, and affluence. For the Indigenous A'uwẽ (Xavante) people in the tropical savannas of Brazil, special forms of intimate and antagonistic social relations, camaraderie, suffering, and engagement with the environment are fundamental aspects of community wellness. Anthropologist James R. Welch transparently presents ethnographic insights from his long-term fieldwork in two A'uwẽ communities. He addresses how distinctive constructions of age organization contribute to social well-being in an era of major ecological, economic, and sociocultural change. Welch shows how A'uwẽ perspectives on the human life cycle help define ethnic identity, promote cultural resilience, and encourage the betterment of youth. They provide frameworks that people may creatively mobilize to responsibly and respectfully engage with others at different stages of life. They also motivate people to access and manage landscape resources essential to the social construction of good living. Through careful analysis, Welch shows how contemporary traditional peoples can foster enthusiasm for service to family and community amid dominant cultures that prioritize individual well-being. This book is an essential resource for students and scholars interested in sociocultural anthropology, Indigenous cultures, health and culture, and human ecology.